Back Cover Image, Volume 2, Number 4, December 2020. Issue 4 (4th December 2020) - Wang, Pengfei; Gong, Zhe; Ye, Ke; Kumar, Vipin; Zhu, Kai; Sha, Linna; Yan, Jun; Yin, Jinling; Cheng, Kui; Wang, Guiling; Cao, Dianxue
Abstract : Back cover image : Lithium‐sulfur batteries attract lots of attention due to their high specific capacity, low cost and environmental friendliness. Wang et al. design and fabricate high sulfur loading electrode with biomass porous carbon current collector and carboxymethyl cellulose binder for high‐performance Li‐S batteries. (10.1002/cey2.49 )